Occurrence of Rare Earth, Iron, Phosphorus and Calcium in High Grade Rare Earth Concentrate - Na Li; Yufang Qin; Hailong Jin; Qiwei Wang (Kuangchan zonghe liyong, 2022)
Rare earth grade of Bayan Obo mixed rare earth concentrate is 65.86%, and the contents of P2O5, CaO and TFe are 11.26%, 3.89% and 1.34%, respectively. Chemical analysis, automatic mineral analysis system, SEM and EDS were used to study the occurrence of rare earth and impurity elements in mixed rare earth concentrate. The results show that rare earth mainly exists in bastnaesite, monazite, parisite and huanghoite in the form of independent minerals, iron mainly exists in magnetite hematite and pyrite， phosphorus mainly exists in monazite and apatite, calcium mainly exists in fluorite, apatite, dolomite and calcite, which can provides mineralogical basis for further separation of bastnaesite and monazite concentrate and reduction of impurity elements in rare earth concentrate.